Book Review on Second Language Teaching and Learning through Virtual Exchange - Li Siying (Journal of China Computer-Assisted Language Learning)
This review briefly introduces an edited volume of recent empirical research on virtual exchange (VE) and second language education. It starts with a general introduction of VE and its potential to fulfil low-boundary interactions in pedagogical instructions, especially during the pandemic. Then it introduces the VE practices in the book from three dimensions: VE and language, VE and culture, as well as VE and teacher development. At last, it affirms the value of VE in improving the efficiency of foreign language education and teacher preparation, and provides suggestions for future studies.